Consumers' demand for red meat attributes in Malaysia - Abdul Hadi, Ahmad Hanis Izani; Selamat, Jinap; Shamsudin, Mad Nasir; Radam, Alias (Faculty of Economics and Management, Universiti Putra Malaysia, 2013)
The growth of Malaysians' per capita income has generally empowered consumers to have wider choices of food, greater purchasing power and as they become more health conscious, they begin to demand for more nutritional food in their daily intake. Motivated by the changes in Malaysian consumer's food choice, a conjoint analysis was performed to investigate the Malaysian consumers' demands for red meat attributes and how much they are willing to pay for their demanded attributes. Two hundred and five respondents from fourteen states in Malaysia were interviewed to rate the combinations of red meat attributes in the range of one to ten, with one as the least preferred, and ten as the most preferred. The findings suggested that the most important attributes for red meat products were texture, followed by freshness, packaging and point of purchase. Consumers were also willing to pay premium prices for the demanded attributes. The results would have positive implications on the agro-food industry if market responds effectively by translating these changes into business opportunities.